Aerodynamics simulation on density jump in a long corridor fire. (August 2015) - Xi, Y.H.; Chow, W.K.; Mao, J.
Graphical abstract: Highlights: Density jump at the smoke barrier in a long corridor fire was studied numerically. Computational Fluid Dynamics model STAR-CCM+ was used. CFD results further confirm that density jump accelerates air entrainment rate. Density jump should be considered in fire hazard assessment of long corridors. Abstract: A density jump occurs when the smoke flowing under the ceiling of a long corridor hits a smoke barrier. Additional air entrainment will increase the mass flow rates of hot smoke. In this paper, density jump at the smoke barrier in a long corridor fire will be studied numerically with a grid system of up to 6.52 million cells, using the Computational Fluid Dynamics (CFD) model STAR-CCM+. Eleven sets of scenarios with a total of 32 numerical experiments were conducted on long corridors of varying width, with a smoke barrier at different heights, and under different hot air and smoke speeds. Predicted results by CFD will be discussed and compared with the analytical expressions of density jump. CFD results further confirm that density jump accelerates air entrainment rate. Additional air entrainment rate into the jump depends on the dimensionless obstruction height to contraction ratio and the upstream Froude number. The phenomenon of density jump should be taken into account in the fire hazard assessment of long corridors.